Clinical usefulness of FDG–PET/CT for the evaluation of various types of adult T-cell leukemia. Issue 9 (21st October 2017) - Nakachi, Sawako; Okada, Masahiro; Morishima, Satoko; Agarie, Yurika; Kitamura, Sakiko; Uchibori, Sachie; Tomori, Shouhei; Hanashiro, Taeko; Shimabukuro, Natsuki; Tamaki, Keita; Tedokon, Iori; Morichika, Kazuho; et al.
ABSTRACT: Purpose: The aim was to explore undefined useful indices for clinically grading adult T-cell leukemia (ATL) using [ 18 F] 2-fluoro-2-deoxyglucose (FDG) – positron emission tomography/computed tomography (PET/CT). Methods: A total of 28 patients with ATL (indolent, 9; aggressive, 19) were enrolled; all patients with aggressive ATL underwent FDG–PET/CT before chemotherapy. Patients with indolent ATL underwent FDG–PET/CT at the time of suspected disease progression and/or transformation; some received lymph node biopsy. The quantitative parameters maximum standardized uptake values (SUVmax), and mean and peak SUV, metabolic tumor volume (MTV), and volume-based total lesion glycolysis were calculated with the margin threshold as 25%, and 50% of the SUVmax for all lesions. Results: All parameters except for MTV-25% showed significant differences ( P  ≤ 0.05) in differentiating the aggressive type from the indolent type of ATL. Areas under the curve for receiver-operating characteristic (ROC) analysis regarding the series of parameters investigated ranged from 0.75 to 0.92; this indicated relatively high accuracy in distinguishing the aggressive type from the indolent type. No malignant findings were detected in lymph node biopsies in indolent ATL patients with lymphadenopathy. Discussion: We performed evaluation of a line of parameters of FDG–PET, thereby demonstrating their significantly high accuracy for grading malignancy in ATL patients. In particular, low accumulation of FDG in indolent ATL patients with lymphadenopathy might predict that it is not a sign of disease transformation, but rather a reactive manifestation. Conclusion: FDG–PET/CT findings could be useful for clinically grading ATL. GRAPHICAL ABSTRACT: